Hegemoni Kekuasaan dalam Novel Surat-Surat dari Dili Karya Maria Matildis Banda - Dayanti, Mey; Mas Triadnyani, I G.A.A. (Humanis; Vol 23 No 1 (2019)DO - 10.24843/JH.2019.v23.i01.p12, 2019)
Entitled with “Hegemony of Power in The Novel Surat-Surat dari Dili Creation by Maria Matildis Banda”. This research purpose are to know the structure and the hegemony that contained in the novel Surat-Surat dari Dili. There are three theories used in this research, which are structural theory by A. Teeuw,  sociology of literature theory by Sapardi Djoko Damono, and the theory of hegemony by Raymond Williams. The method used in data collection are litereture study method which completed by technique note. Then continue using formal and informal methods to analyze the data. Furthermore, qualitative and quantitative method used as the presentation process of analysis data result, which are by interpreting and presenting data in the form of descriptions, tables, and diagrams. There are some revelation obtained based on the analysis in the novel Surat-Surat dari Dili. Firstly, in structural analysis that includes plot, characterization, and setting, they have relationships that related to each other. The relationship between the elements leads the reader to a theme, the hegemony of power. Secondly, the hegemony of the novel is divided into three processes, namely causes, implementation, and consequences. All three processes visible on events that occur , such as rape, put someone in jail, murder, and tragedy.